Aberrant maspin expression in gallbladder epithelium is associated with intestinal metaplasia in patients with cholelithiasis. Issue 3 (27th February 2006) - Maesawa, C; Ogasawara, S; Yashima-Abo, A; Kimura, T; Kotani, K; Masuda, S; Nagata, Y; Iwaya, T; Suzuki, K; Oyake, T; Akiyama, Y; Kawamura, H; et al.
Abstract : Objective: Aberrant expression of maspin protein related to DNA hypomethylation in the promoter region is frequently observed in gallbladder carcinomas, whereas the non-tumorous gallbladder epithelium is maspin negative. We investigated maspin expression in non-tumorous gallbladder epithelium in patients with cholelithiasis. Methods: An immunohistochemical study of maspin expression was performed in 69 patients with cholelithiasis and 30 patients with gastric cancer without cholelithiasis. Results: Immunoreactivity for maspin was observed in focal and patchy regions of the gallbladder epithelium. Positive immunoreactivity for maspin was significantly associated with the presence of intestinal metaplasia in patients with cholelithiasis (p<0.05). Conclusion: The high incidence of aberrant maspin expression in both intestinal metaplasia and carcinoma of the gallbladder supports the assumption that intestinal metaplasia of the gallbladder may predispose to gallbladder carcinoma.